Divergent selection for residual feed intake in group-housed growing pigs: characteristics of physical and behavioural activity according to line and sex. (24th July 2014) - Meunier-Salaün, M. C.; Guérin, C.; Billon, Y.; Sellier, P.; Noblet, J.; Gilbert, H.
<x content-type="archive" xml:space="preserve">Abstract</x> The aim of the study was to assess the impact of selection for residual feed intake (RFI) on the behavioural activity of lines divergently selected for RFI during seven generations. In all, six successive batches from the seventh generation of selection were raised in collective pens equipped with a single-place electronic feeder (SEF) from 10 weeks of age to 100 kg BW. Each batch included four groups of 12 pigs: high RFI (RFI+) castrated males, RFI+ females, low RFI (RFI−) castrated males, RFI− females. At 17 weeks of age, health criteria were evaluated using a gradient scale for increased severity of lameness, body lesions, bursae and tail biting. Individual behavioural activities were recorded by 24-h video tape on the day after health evaluation. The investigative motivation towards unfamiliar objects was quantified at 18 weeks of age. The daily individual feeding patterns were computed from SEF records during the 4 weeks surrounding 12, 17 and 22 weeks of age. All pigs spent significantly most of their time lying in diurnal (80% of total scan) and nocturnal (>89%) periods. The RFI− pigs showed a lower proportion of health problems (P<0.01) than RFI+ pigs. The RFI− pigs used the SEF less than the RFI+ pigs, in diurnal (5.3% v. 6.4% of video scans, P<0.05) and nocturnal periods (3.6% v. 4.5% of video scans, P<0.05). This was confirmed by a significantly lower daily number and duration of visits to the SEF computed from the SEF data. The feeding activity measured from the video recording was significantly correlated (R>0.34; P<0.05) with feeding patterns computed from the SEF. The RFI− pigs spent less time standing over the 24-h period (9.7% v. 12.2% of scans, i.e. 35 min/day, P<0.05). In terms of energy costs, this amounted to 14% of the line difference in terms of daily metabolizable energy intake. The castrated males used the SEF more than females, especially at night (4.7% v. 3.4% of total scans, P<0.05), whereas females displayed greater investigation of their environment (7.7±0.3% v. 6.6±0.2% of total scans, P<0.05) and the novel objects (10.7% v. 4.9% of total scans, P<0.05). In conclusion, the lower physical activity associated with reduced energy expenditure in RFI− pigs compared with RFI+ pigs contributed significantly to their improved efficiency and was not related to worsened health scores.